2013
DOI: 10.1093/jrr/rrt087
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the strength of iodine-125 seed moving at unknown speed during implantation in brachytherapy

Abstract: The aim of this study is to demonstrate the feasibility of estimating the strength of the moving radiation source during patient implantation. The requirement for the counting time was investigated by comparing the results of the measurements for the static source with those for the source moving at 2, 5, 10 and 20 cm s−1. The utilized source was 125I with an air-kerma strength of 0.432 U (μGym2h–1). The detector utilized was a plastic scintillation detector (8 cm × 5 cm × 2 cm in thickness) set at 8 cm away f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…Similarly, the length of the region in which the change in the counting rate was ~10% was ~30 to 50 mm. These lengths are comparable to those in the previous study [ 9 ]. The previous study showed the uncertainty from a source speed variation of 2–20 cm/s was within 2.3% for a counting time of 50 ms [ 9 ].…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Similarly, the length of the region in which the change in the counting rate was ~10% was ~30 to 50 mm. These lengths are comparable to those in the previous study [ 9 ]. The previous study showed the uncertainty from a source speed variation of 2–20 cm/s was within 2.3% for a counting time of 50 ms [ 9 ].…”
Section: Resultssupporting
confidence: 90%
“…These lengths are comparable to those in the previous study [ 9 ]. The previous study showed the uncertainty from a source speed variation of 2–20 cm/s was within 2.3% for a counting time of 50 ms [ 9 ]. In this study, the source speed was assumed to be 10–20 cm/s.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…If necessary, the dose could then be reduced by increasing the distance between the sources. The estimation method proposed here has previously been suggested for use in loose 125 I source implants [ 9 , 10 ]. In the present study, this method has been applied to linked sources.…”
Section: Introductionmentioning
confidence: 99%